Enhancing the mechanical performance of laser-welded Al–Si coated 22MnB5 PHS via dilution-controlled nickel addition - Xuzhi Zhang; Jiazhuang Tian; Wu Tao; Yanjun Wang; Jiazhi Zhang; Yanjie Sun; Shanglu Yang (Journal of Materials Research and Technology)
Al–Si coated 22MnB5 press-hardened steel (PHS) has been dramatically applied in new energy vehicles, whereas the Al–Si coating dilution into the laser weld usually leads to the formation of a large amount of ferrite in laser-welded joints, which induces poor mechanical properties. In this study, a new low-cost, high-strength steel filler wire was patented and applied to control the dilution rate of Al–Si coating in the welded joints. Hardness and tensile tests were performed, coupled with microstructure observation (scanning electron microscopy and electron backscatter diffraction). Results indicate that when the dilution rate is no higher than 80 %, the increased nickel (Ni) content in the weld markedly decreases ferrite formation during the peritectic reaction, increasing the formation of high-dislocation-density martensite and the proportion of low-angle grain boundaries. The developed approach demonstrates enhanced efficacy in fabricating Al–Si coated PHS tailor-welded components, as evidenced by improved elongation and a transition in fracture location from the weld zone to the base metal.